Periodontolojide postoperatif Ağrı - KURU, LEYLA; YILDIRIM, HATİCE SELİN (Türkiye Klinikleri Yayınevi, 2023)
ÖZET Periodontal tedavi işlemleri sırasında veya sonrasında hastalarda ağrı, rahatsızlık ve dentin hassasiyetiduyabileceği beklentisi vardır. Periodontal tedavinin en yaygın uygulanan ve ilk basamağı olandiş yüzeyi temizliği ve kök yüzeyi düzleştirmesi prosedüründe, belirli bir süre hafif ağrı duyulabilmektedir.Periodontal cerrahi tedavilerde ise daha şiddetli ağrı ve rahatsızlık hissi oluşabilmektedir. Ağrıtüm periodontal cerrahi uygulamalarının kaçınılmaz doğal bir sonucudur. Yapılan tüm periodontal tedaviişlemlerinde, hasta konforu ve memnuniyetini artırmak, hastanın tedaviye uyumunu ve iş birliğini sağlamakiçin işlemler sırasında ve sonrasında duyulan ağrıyı azaltmak büyük önem taşımaktadır. Periodontaltedavinin başarısı sadece uygun cerrahi tekniğin seçilmesi ve uygulanmasına değil aynı zamandaağrı başta olmak üzere postoperatif komplikasyonların önlenmesi ve kontrolüne de bağlıdır.Anah tar Ke li me ler: Periodontal hastalıklar; oral cerrahi işlemler; postoperatif ağrıABS TRACT During and following several periodontal procedures, it is normal for patients to experiencediscomfort, postoperative pain, and dentin hypersensitivity. The scaling and root planing procedure,which is the most frequently used treatment and first step of periodontal therapy, may causediscomfort lasting for a short time. Periodontal surgical therapy results in more severe pain and discomfort.Pain is an inevitable outcome of all periodontal surgical procedures. Therefore, it is crucial tolessen the postoperative pain of the patient in order to improve overall level of comfort and satisfaction,promote collaboration and treatment compliance. In addition to application of the proper surgical technique,the effectiveness of periodontal surgery depends on prevention and management of pain and otherpostoperative complications.Keywords: Periodontal diseases; oral surgical procedures; postoperative pain

During and following several periodontal procedures, it is normal for patients to experience discomfort, postoperative pain, and dentin hypersensitivity. The scaling and root planing procedure, which is the most frequently used treatment and first step of periodontal therapy, may cause discomfort lasting for a short time. Periodontal surgical therapy results in more severe pain and discomfort. Pain is an inevitable outcome of all periodontal surgical procedures. Therefore, it is crucial to lessen the postoperative pain of the patient in order to improve overall level of comfort and satisfaction, promote collaboration and treatment compliance. In addition to application of the proper surgical technique, the effectiveness of periodontal surgery depends on prevention and management of pain and other postoperative complications.
Postoperative pain in Periodontology
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); During and following several periodontal procedures; it is normal for patients to experience discomfort; postoperative pain; and dentin hypersensitivity. The scaling and root planing procedure; which is the most frequently used treatment and first step of periodontal therapy; may cause discomfort lasting for a short time. Periodontal surgical therapy results in more severe pain and discomfort. Pain is an inevitable outcome of all periodontal surgical procedures. Therefore; it is crucial to lessen the postoperative pain of the patient in order to improve overall level of comfort and satisfaction; promote collaboration and treatment compliance. In addition to application of the proper surgical technique; the effectiveness of periodontal surgery depends on prevention and management of pain and other postoperative complications.; Periodontal diseases; oral surgical procedures